If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 89 = 29 Reorder the terms: 89 + 5x = 29 Solving 89 + 5x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-89' to each side of the equation. 89 + -89 + 5x = 29 + -89 Combine like terms: 89 + -89 = 0 0 + 5x = 29 + -89 5x = 29 + -89 Combine like terms: 29 + -89 = -60 5x = -60 Divide each side by '5'. x = -12 Simplifying x = -12
| 2u+91=27 | | -7+0.25m=7 | | 0.8x+23=-25 | | 2x+24=18 | | 0.8x+23=25 | | -16a+67=3 | | 7x-35-3x=2x-13 | | 2x+24=78 | | 5c+17=2 | | -7v+81=32 | | -7v+81=7 | | 9b+50=275 | | 5y-10=-35 | | 25+11.12b=47 | | -2h+7=45 | | 6(4x-6)+18=6 | | 3s+158=-16 | | 8(x-4)-18=22 | | 7t+55=-246 | | 3-4x=-7+6x | | f(x)=8(x-4)-18 | | 3f+65=14 | | 3x+8x-40=360 | | 8a+79=7 | | -108=-5(6n-1)+7 | | 10-i= | | 6W+192=55 | | 0.8x-23=25 | | 53-7j=18 | | 30-2h=182 | | y=11x+b | | 130-11g=20 |